GPA Comparison of Students Admission in SNMPTN and SBMPTN in Department of Physics Education FKIP Unsyiah - Afra Mulya Alamsyah; Susanna Susanna; Evendi Evendi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2020)
The comparative research with a quantitative approach aims to find out the comparison of the GPA of student admission the SNMPTN and SBMPTN entry points at the Department of Physics Education FKIP Unsyiah. The sample in this study were students of Physics Education 2017-2018 who admission form the SNMPTN 47 students and the SBMPTN 57 students. The collection of research data through the documentation method of admission and transcripts of students grades at the Department of Physics Education FKIP Unsyiah. Analysis and processing data using comparative analysis for two different samples (independent) with using the two samples t-tests. The result of ttest (t0) = 0,71 and ttable (tα) = 1,980. The conclusion in the study, there is no difference in the GPA of students who pass through the SNMPTN and SBMPTN entrance lines at the Department of Physics Education FKIP Unsyiah for the 2017-2018 class.